The Effect of Jigsaw Cooperative Learning Method on Students Performance in the Class Assessment Test (CAT): A Quasi Experimental Study - Ghouri, Aftab; Rehman, Abdul; Zaman, Muhammad; Anum, Sheeraz; Masih, Imran; Shahjhan, Zuhra (Journal of Liaquat University of Medical & Health Sciences, 2022)
OBJECTIVE: To evaluate the difference between jigsaw cooperative learning and the traditional method on the students' performance in the CAT. METHODOLOGY: This quasi-experimental study was completed at Indus College of Nursing & Midwifery Karachi. The data was collected from April to September 2021. The total sample size was 60. Male and female of 3rd year nursing students were included. The participants were approached by using the nonprobability consecutive sampling method. SPSS version 22.0 was used for data entry and interpretation. RESULTS: Out of 60 participants, 52% were male. A large number of 49 (82%) respondents were between18-22. Thirty-one subjects (52%) education level was matriculation. A significant difference was found between pre and post-test(7.03±2.44 & 14.48±2.45) of both traditional (lecture) and jigsaw groups with substantial (0.00) p-value. Gender knowledge found dissimilarity that females of study slightly remained at higher side than men in pre-test and post-test of knowledge and both conditions p-value was insignificant. CONCLUSION: It was concluded that the participants' knowledge was measured with a paired t-test, which result is similar in both groups, but no difference was found in the lecture and jigsaw method among participants. KEYWORDS: Jigsaw Method, Traditional Teaching Method, Student's Performance